Did Openness and Human Capital Affect Total Factor Productivity? Evidence from the South Asian Region. (May 2014) - Rath, Badri Narayan; Parida, Purna Chandra
This article examines the impact of human capital and openness on total factor productivity (TFP) for five South Asian countries—India, Pakistan, Sri Lanka, Bangladesh, and Nepal—during the period from 1980 to 2011. The empirical results derived from the panel cointegration techniques provide evidence of a long-run relationship among the variables. The dynamic ordinary least squares (DOLS) results show that the long-run elasticities of TFP with respect to human capital and openness are positive. The results, however, suggest that the impact of human capital on TFP is relatively weaker than the impact of openness on TFP for the South Asian countries. The study also examines the long-run and short-run Granger causality between these three variables in a panel framework. The results indicate that there is a long-run Granger causality running from trade openness and human capital to TFP. Similarly, in the short-run, there exists a bi-directional Granger causality between trade openness and total factor productivity and between total factor productivity and human capital. The study suggests that by improving trade policy reforms, such as, licensing policies, and removing trade barriers, the low-income countries in South Asia can increase their level of openness, which would boost the TFP in the short run.